Continuous casting high-hardness acrylic plate and preparation method thereof
By forming a high-hardness coating on the outside of the acrylic sheet, the problems of low hardness and poor wear resistance of the acrylic sheet are solved, a balance between hardness and transparency is achieved, and the use effect of the material is improved.
Patent Information
- Application Number
- CN202511258675.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-09-04
AI Technical Summary
The existing acrylic sheet has low surface hardness and poor wear resistance, and is easily scratched, resulting in reduced transparency and affecting the use effect.
Siloxane-modified methacrylic acid and methyl methacrylate are used as modified monomers, and a high-hardness coating is formed through terminal hydroxy ether polysiloxane, isophorone diisocyanate and N-hydroxymethyl acrylamide. UV curing technology is used to form a high-hardness layer on the outside of the acrylic plate to improve hardness and transparency.
While increasing the hardness of the acrylic sheet, it maintains or improves its transparency, forming a high-hardness and transparent coating, enhancing the wear resistance and service life of the material.
Smart Images

Figure CN120718306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of acrylic plates, and in particular relates to a continuously cast high-hardness acrylic plate and a preparation method thereof. Background Art
[0002] Acrylic sheet is made from the polymerization of methyl methacrylate monomers. Its chemical name is polymethyl methacrylate (PMMA). Due to its excellent light transmittance, it is also known as organic glass. Acrylic sheet has the characteristics of good light transmittance, resistance to cracking, good toughness, easy cleaning, and soft texture.
[0003] However, the existing acrylic sheet has low surface hardness and poor wear resistance. The surface is easily scratched during use, causing the surface to fog and reduce the transparency of the material, which limits the use of the product.
[0004] Publication number CN118496613A discloses a high-hardness and high-wear-resistant acrylic material and a preparation method thereof. Silane liquid is combined with glycolic acid to form a silane-modifying liquid to modify the interface of a blending agent, a flaky graphene modifier, and a polymethyl methacrylate raw material. The blending agent and the flaky graphene modifier coordinate with each other and reinforce each other, thereby enhancing the hardness, wear resistance, and mechanical strength properties of the product.
[0005] However, simply increasing the hardness by adding inorganic materials to methyl methacrylate monomers may result in a decrease in the transparency of the material, which also affects the use of the material. Summary of the Invention
[0006] The object of the present invention is to provide a continuous casting high-hardness acrylic plate and a preparation method thereof to solve the above technical problems.
[0007] In order to achieve the above technical objectives, the technical solution of the present invention is: The method for preparing a continuous casting high-hardness acrylic plate comprises the following steps: S1, mixing siloxane-modified methacrylic acid, methyl methacrylate, and n-butyl methacrylate, adding an azo initiator thereto, and stirring and mixing to obtain a prepolymer slurry; S2, mixing the hydroxy-terminated ether polysiloxane, isophorone diisocyanate and the catalyst dibutyltin dilaurate, and reacting them under magnetic stirring at room temperature for 4 to 6 hours to obtain a macromolecular prepolymer, and then adding the end-capping agent N-hydroxymethyl acrylamide and the photoinitiator 2-hydroxy-2-methylpropiophenone thereto, and continuing to stir at room temperature in the dark for 2 hours to obtain a coating slurry; S3. The prepolymer slurry is injected between two synchronously running endless steel belts, and the coating slurry is coated on the two endless steel belts at the same time. During the operation of the endless steel belts, the prepolymer slurry is continuously polymerized through the first polymerization zone and the second polymerization zone, and then is kept warm in the heat preservation zone and cooled in the cooling zone to obtain an acrylic plate coated with the coating slurry. The acrylic plate coated with the coating slurry is cured by ultraviolet light to obtain a high-hardness acrylic plate.
[0008] As a further improvement, in step S1, the volume ratio of the siloxane-modified methacrylic acid to methyl methacrylate is 1-1.2:9, and the n-butyl methacrylate accounts for 1-20% of the total volume of the methyl methacrylate and n-butyl methacrylate.
[0009] As a further improvement, in step S1, the preparation method of the siloxane-modified methacrylic acid is as follows: drying a condenser, a stirrer, and a three-necked flask in an oven at 120° C. for 2 hours, assembling them while hot and purging them with nitrogen, adding γ-glycidoxypropyltrimethoxysilane and methacrylic acid thereto, adding a catalyst triethylamine and a polymerization inhibitor hydroquinone thereto under stirring, reacting at 95° C. to 105° C. for 4 to 8 hours, cooling to room temperature after completion of the reaction, adding deionized water to quench the catalyst, washing the reactants with water, and then standing to separate the layers, separating the organic phase and drying it to obtain the siloxane-modified methacrylic acid.
[0010] As a further improvement, the molar ratio of the γ-glycidoxypropyltrimethoxysilane and methacrylic acid is 1:1~1.05, the amount of the triethylamine added is 0.6% of the total mass of the γ-glycidoxypropyltrimethoxysilane and methacrylic acid, and the mass ratio of the hydroquinone to the triethylamine is 2:15.
[0011] As a further improvement, the UV curing is specifically as follows: the acrylic plate coated with the coating slurry is polymerized under 365nm UV light for 2 to 2.5 hours, then immersed in an ethanol-water mixed solution for 30 to 45 minutes, then immersed in distilled water for 24 hours, and finally dried at 60°C.
[0012] As a further improvement, the temperature of the first polymerization zone is 60~80℃, and the polymerization time is 5~1440min; the polymerization temperature of the second polymerization zone is 100~140℃, and the polymerization time is 5~1440min; the temperature of the insulation zone is 100~140℃, and the insulation time is 5~1440min.
[0013] As a further improvement, in step S2, the preparation method of the terminal hydroxy ether polysiloxane is: terminal hydrogen silicone oil and allyl hydroxyethyl ether are mixed and stirred uniformly, heated to 50°C, Karstedt catalyst is added thereto, and then heated to 60-70°C for reaction for 3-4 hours. After the reaction is completed, pressure rotary evaporation is performed at 10-50 mbar to obtain the terminal hydroxy ether polysiloxane.
[0014] As a further improvement, the hydrogen content of the hydrogen-terminated silicone oil is 0.11-0.13%, the molar ratio of the hydrogen-terminated silicone oil to the allyl hydroxyethyl ether is 1:2, and the amount of the Karstedt catalyst added is 0.15-0.2% of the total mass of the hydrogen-terminated silicone oil and the allyl hydroxyethyl ether.
[0015] As a further improvement, in step S2, the molar ratio of the terminal hydroxy ether polysiloxane, isophorone diisocyanate and N-hydroxymethyl acrylamide is 1:1.5:1, the amount of the photoinitiator added is 0.2% of the total mass of the terminal hydroxy ether polysiloxane and isophorone diisocyanate, and the mass ratio of the catalyst to the photoinitiator is 0.1~0.3:2.
[0016] The present invention also provides a continuously cast high-hardness acrylic plate.
[0017] Due to the adoption of the above technical solution, the present invention has the following beneficial effects: The present invention provides a continuously cast high-hardness acrylic plate and a preparation method thereof. A prepolymer is prepared using terminal hydroxy ether polysiloxane and isophorone diisocyanate as monomers and N-hydroxymethyl acrylamide as a capping agent. A high-hardness layer is formed on the outside of the acrylic plate by ultraviolet curing. Polyurethane is modified with the terminal hydroxy ether polysiloxane. The polysiloxane chain segment increases the rigidity of the soft segment, thereby increasing the hardness of the polyurethane.
[0018] The present invention uses siloxane-modified methacrylic acid as a modifying monomer to copolymerize and modify the acrylic sheet. On the one hand, the siloxane in the modified monomer can improve the hardness of the acrylic sheet. On the other hand, the hydroxyl group in the modified monomer enables hydrogen bonds to be formed between the molecules of the polymer macromolecules, thereby increasing the intermolecular force and further improving the hardness of the acrylic sheet.
[0019] In the present invention, the modified monomers siloxane-modified methacrylic acid and methyl methacrylate adopt a specific volume ratio, which has little effect on the transparency of the acrylic plate, and does not affect the transparency while improving the hardness of the acrylic plate.
[0020] In the preparation process of the high hardness layer of the present invention, N-hydroxymethyl acrylamide is used as a capping agent. The presence of amide groups can increase the interaction between polymer molecules in the high hardness layer, thereby further improving the hardness of the high hardness layer.
[0021] In the preparation process of the high-hardness layer of the present invention, terminal hydroxy ether polysiloxane is used, and the alkyl ether structure therein can improve the mutual solubility between the oil-phase polymerization network and the hydrophilic monomer of the capping agent, thereby improving the overall uniformity and compatibility of the polymer network, avoiding the reduction in transparency caused by the poor compatibility between the oil-phase polymerization network and the capping agent due to the amide group, and the obtained high-hardness layer also has high transparency under the condition of high hardness. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the endless steel belt. DETAILED DESCRIPTION
[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or the conditions recommended by the manufacturer. Those whose reagents or instruments are not specified by the manufacturer are conventional products that can be purchased commercially.
[0024] In the present invention, the hydrogen content of the hydrogen-terminated silicone oil is 0.11-0.13%, and the molar mass thereof is 1550-1832 g / mol.
[0025] Example 1 A method for preparing a continuously cast high-hardness acrylic plate comprises the following steps: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 43.05 g (0.5 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine (TEA) and 0.13 g of polymerization inhibitor hydroquinone under stirring, and react at 95°C for 8 hours. After the reaction is completed, cool to room temperature, add 20 mL of deionized water to quench the catalyst, wash the reactants with water, let them stand and separate, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; The specific reaction equation is as follows: ; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 55.56 mL of the modifying monomer, and 5.05 mL of n-butyl methacrylate were mixed, 0.56 g of azobisisobutyronitrile as an initiator was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3. 15.5 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether were mixed and stirred uniformly, the temperature was raised to 50° C., 0.026 g of Karstedt catalyst was added thereto, and the temperature was raised to 60° C. to react for 4 h. After the reaction was completed, the mixture was subjected to rotary evaporation at 10 mbar to obtain terminal hydroxy ether polysiloxane; The specific reaction equation is as follows: ; S4. 17.54 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate, and 2.10 mg of catalyst dibutyltin dilaurate were mixed and reacted at room temperature under magnetic stirring for 4 h to obtain a macromolecular prepolymer. 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.042 g of photoinitiator 2-hydroxy-2-methylpropiophenone were then added thereto, and stirring was continued at room temperature in the dark for 2 h to obtain a coating slurry. S5. Injecting prepolymer slurry between two synchronously running endless steel belts and simultaneously coating the outer walls of the two endless steel belts with coating slurry. During the movement of the endless steel belts, the prepolymer slurry sequentially passes through a first polymerization zone, a second polymerization zone, a heat preservation zone, and a cooling zone to obtain an acrylic sheet coated with the coating slurry. The continuous casting preparation method of the acrylic sheet is an existing technology. The temperature of the first polymerization zone is 60°C and the polymerization time is 1440 min; the temperature of the second polymerization zone is 100°C and the polymerization time is 1440 min; the temperature of the holding zone is 100°C and the holding time is 1440 min; S6. Place the acrylic plate coated with the coating slurry in a 365nm UV lamp box to initiate polymerization for 2 hours, then soak it in an ethanol-water mixed solution (the volume ratio of ethanol to water is 1:1), soak it in distilled water for 24 hours after 30 minutes, and finally dry it at 60°C to obtain a high-hardness acrylic plate.
[0026] In this embodiment, the schematic diagram of the annular steel belt is as follows Figure 1 shown.
[0027] In this embodiment, after the coating slurry is photocured, a high-hardness layer is formed on the outside of the acrylic plate. The acrylic plate obtained in this embodiment has high hardness and good transparency due to the adhesion of the high-hardness layer.
[0028] Example 2 A method for preparing a continuously cast high-hardness acrylic plate comprises the following steps: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17g (0.5mol) of γ-glycidoxypropyltrimethoxysilane and 45.20g (0.525mol) of methacrylic acid, add 0.98g of catalyst triethylamine (TEA) and 0.13g of polymerization inhibitor hydroquinone under stirring, react at 105°C for 4 hours, cool to room temperature after the reaction is completed, add 20mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 66.67 mL of the modifying monomer, and 125 mL of n-butyl methacrylate were mixed, 0.69 g of azobisisoheptanenitrile as an initiator was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3. 18.32 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether were mixed and stirred uniformly, the temperature was raised to 50° C., 0.041 g of Karstedt catalyst was added thereto, and the temperature was raised to 70° C. to react for 3 h. After the reaction was completed, the mixture was subjected to pressure rotary evaporation at 50 mbar to obtain terminal hydroxy ether polysiloxane; S4. 20.36 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate, and 7.05 mg of catalyst dibutyltin dilaurate were mixed and reacted at room temperature under magnetic stirring for 6 h to obtain a macromolecular prepolymer. 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.047 g of photoinitiator 2-hydroxy-2-methylpropiophenone were then added thereto, and stirring was continued at room temperature in the dark for 2 h to obtain a coating slurry. S5, injecting the prepolymer slurry between two synchronously running endless steel belts, and simultaneously coating the outer walls of the two endless steel belts with the coating slurry. During the movement of the endless steel belts, the prepolymer slurry sequentially passes through the first polymerization zone, the second polymerization zone, the heat preservation zone, and the cooling zone to obtain an acrylic sheet coated with the coating slurry; The temperature of the first polymerization zone is 80°C and the polymerization time is 5 minutes; the temperature of the second polymerization zone is 140°C and the polymerization time is 5 minutes; the temperature of the holding zone is 140°C and the holding time is 5 minutes; S6. Place the acrylic plate coated with the coating slurry in a 365nm UV lamp box to initiate polymerization for 2.5 hours, then soak it in an ethanol-water mixed solution (the volume ratio of ethanol to water is 1:1), soak it in distilled water for 24 hours after 45 minutes, and finally dry it at 60°C to obtain a high-hardness acrylic plate.
[0029] Example 3 A method for preparing a continuously cast high-hardness acrylic plate comprises the following steps: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 44.12 g (0.5125 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine (TEA) and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 100°C for 6 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 61.11 mL of the modifying monomer, and 111.11 mL of n-butyl methacrylate were mixed, 0.67 g of initiator dimethyl azobisisobutyrate was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3. 17.00 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether were mixed and stirred uniformly, the temperature was raised to 50° C., 0.034 g of Karstedt catalyst was added thereto, and the temperature was raised to 65° C. for reaction for 3.5 h. After the reaction was completed, the mixture was subjected to pressure rotary evaporation at 30 mbar to obtain terminal hydroxy ether polysiloxane; S4. 19.04 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate, and 4.5 mg of catalyst dibutyltin dilaurate were mixed and reacted under magnetic stirring at room temperature for 5 h to obtain a macromolecular prepolymer. 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.045 g of photoinitiator 2-hydroxy-2-methylpropiophenone were then added thereto, and stirring was continued at room temperature in the dark for 2 h to obtain a coating slurry. S5, injecting the prepolymer slurry between two synchronously running endless steel belts, and simultaneously coating the outer walls of the two endless steel belts with the coating slurry. During the movement of the endless steel belts, the prepolymer slurry sequentially passes through the first polymerization zone, the second polymerization zone, the heat preservation zone, and the cooling zone to obtain an acrylic sheet coated with the coating slurry; The temperature of the first polymerization zone is 70°C and the polymerization time is 1000 min; the temperature of the second polymerization zone is 120°C and the polymerization time is 1000 min; the temperature of the holding zone is 120°C and the holding time is 1000 min; S6. Place the acrylic plate coated with the coating slurry in a 365nm UV lamp box to initiate polymerization for 2.3 hours, then soak it in an ethanol-water mixed solution (the volume ratio of ethanol to water is 1:1). After 38 minutes, soak it in distilled water for 24 hours, and finally dry it at 60°C to obtain a high-hardness acrylic plate.
[0030] Example 4 A method for preparing a continuously cast high-hardness acrylic plate comprises the following steps: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 44.12 g (0.5125 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine (TEA) and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 100°C for 6 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 63.89 mL of the modifying monomer, and 105.26 mL of n-butyl methacrylate were mixed, 0.67 g of initiator dimethyl azobisisobutyrate was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3. 17.00 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether were mixed and stirred uniformly, the temperature was raised to 50° C., 0.034 g of Karstedt catalyst was added thereto, and the temperature was raised to 65° C. for reaction for 3.5 h. After the reaction was completed, the mixture was subjected to pressure rotary evaporation at 30 mbar to obtain terminal hydroxy ether polysiloxane; S4. 19.04 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate, and 4.5 mg of catalyst dibutyltin dilaurate were mixed and reacted under magnetic stirring at room temperature for 5 h to obtain a macromolecular prepolymer. 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.045 g of photoinitiator 2-hydroxy-2-methylpropiophenone were then added thereto, and stirring was continued at room temperature in the dark for 2 h to obtain a coating slurry. S5, injecting the prepolymer slurry between two synchronously running endless steel belts, and simultaneously coating the outer walls of the two endless steel belts with the coating slurry. During the movement of the endless steel belts, the prepolymer slurry sequentially passes through the first polymerization zone, the second polymerization zone, the heat preservation zone, and the cooling zone to obtain an acrylic sheet coated with the coating slurry; The temperature of the first polymerization zone is 65°C and the polymerization time is 500 min; the temperature of the second polymerization zone is 115°C and the polymerization time is 500 min; the temperature of the holding zone is 115°C and the holding time is 500 min; S6. Place the acrylic plate coated with the coating slurry in a 365nm UV lamp box to initiate polymerization for 2.2 hours, then soak it in an ethanol-water mixed solution (the volume ratio of ethanol to water is 1:1). After 38 minutes, soak it in distilled water for 24 hours, and finally dry it at 60°C to obtain a high-hardness acrylic plate.
[0031] Example 5 A method for preparing a continuously cast high-hardness acrylic plate comprises the following steps: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 44.12 g (0.5125 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine (TEA) and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 100°C for 6 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 58.33 mL of the modifying monomer, and 117.65 mL of n-butyl methacrylate were mixed, 0.68 g of initiator dimethyl azobisisobutyrate was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3. 17.00 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether were mixed and stirred uniformly, the temperature was raised to 50° C., 0.034 g of Karstedt catalyst was added thereto, and the temperature was raised to 65° C. for reaction for 3.5 h. After the reaction was completed, the mixture was subjected to pressure rotary evaporation at 30 mbar to obtain terminal hydroxy ether polysiloxane; S4. 19.04 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate, and 4.5 mg of catalyst dibutyltin dilaurate were mixed and reacted under magnetic stirring at room temperature for 5 h to obtain a macromolecular prepolymer. 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.045 g of photoinitiator 2-hydroxy-2-methylpropiophenone were then added thereto, and stirring was continued at room temperature in the dark for 2 h to obtain a coating slurry. S5, injecting the prepolymer slurry between two synchronously running endless steel belts, and simultaneously coating the outer walls of the two endless steel belts with the coating slurry. During the movement of the endless steel belts, the prepolymer slurry sequentially passes through the first polymerization zone, the second polymerization zone, the heat preservation zone, and the cooling zone to obtain an acrylic sheet coated with the coating slurry; The temperature of the first polymerization zone is 65°C and the polymerization time is 300 min; the temperature of the second polymerization zone is 115°C and the polymerization time is 300 min; the temperature of the holding zone is 115°C and the holding time is 300 min; S6. Place the acrylic plate coated with the coating slurry in a 365nm UV lamp box to initiate polymerization for 2.2 hours, then soak it in an ethanol-water mixed solution (the volume ratio of ethanol to water is 1:1). After 38 minutes, soak it in distilled water for 24 hours, and finally dry it at 60°C to obtain a high-hardness acrylic plate.
[0032] Example 6 A method for preparing a continuously cast high-hardness acrylic plate comprises the following steps: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 44.12 g (0.5125 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine (TEA) and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 100°C for 6 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 58.33 mL of the modifying monomer, and 117.65 mL of n-butyl methacrylate were mixed, 0.68 g of initiator dimethyl azobisisobutyrate was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3. 17.00 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether were mixed and stirred uniformly, the temperature was raised to 50° C., 0.034 g of Karstedt catalyst was added thereto, and the temperature was raised to 65° C. for reaction for 3.5 h. After the reaction was completed, the mixture was subjected to pressure rotary evaporation at 30 mbar to obtain terminal hydroxy ether polysiloxane; S4. 19.04 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate, and 4.5 mg of catalyst dibutyltin dilaurate were mixed and reacted under magnetic stirring at room temperature for 5 h to obtain a macromolecular prepolymer. 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.045 g of photoinitiator 2-hydroxy-2-methylpropiophenone were then added thereto, and stirring was continued at room temperature in the dark for 2 h to obtain a coating slurry. S5, injecting the prepolymer slurry between two synchronously running endless steel belts, and simultaneously coating the outer walls of the two endless steel belts with the coating slurry. During the movement of the endless steel belts, the prepolymer slurry sequentially passes through the first polymerization zone, the second polymerization zone, the heat preservation zone, and the cooling zone to obtain an acrylic sheet coated with the coating slurry; The temperature of the first polymerization zone is 75°C and the polymerization time is 200 min; the temperature of the second polymerization zone is 105°C and the polymerization time is 200 min; the temperature of the holding zone is 105°C and the holding time is 200 min; S6. Place the acrylic plate coated with the coating slurry in a 365nm UV lamp box to initiate polymerization for 2.2 hours, then soak it in an ethanol-water mixed solution (the volume ratio of ethanol to water is 1:1). After 38 minutes, soak it in distilled water for 24 hours, and finally dry it at 60°C to obtain a high-hardness acrylic plate.
[0033] Example 7 A method for preparing a continuously cast high-hardness acrylic plate comprises the following steps: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 44.12 g (0.5125 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine (TEA) and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 100°C for 6 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 58.33 mL of the modifying monomer, and 117.65 mL of n-butyl methacrylate were mixed, 0.68 g of initiator dimethyl azobisisobutyrate was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3. 17.00 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether were mixed and stirred uniformly, the temperature was raised to 50° C., 0.034 g of Karstedt catalyst was added thereto, and the temperature was raised to 65° C. for reaction for 3.5 h. After the reaction was completed, the mixture was subjected to pressure rotary evaporation at 30 mbar to obtain terminal hydroxy ether polysiloxane; S4. 19.04 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate, and 4.5 mg of catalyst dibutyltin dilaurate were mixed and reacted under magnetic stirring at room temperature for 5 h to obtain a macromolecular prepolymer. 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.045 g of photoinitiator 2-hydroxy-2-methylpropiophenone were then added thereto, and stirring was continued at room temperature in the dark for 2 h to obtain a coating slurry. S5, injecting the prepolymer slurry between two synchronously running endless steel belts, and simultaneously coating the outer walls of the two endless steel belts with the coating slurry. During the movement of the endless steel belts, the prepolymer slurry sequentially passes through the first polymerization zone, the second polymerization zone, the heat preservation zone, and the cooling zone to obtain an acrylic sheet coated with the coating slurry; The temperature of the first polymerization zone is 75°C and the polymerization time is 100 min; the temperature of the second polymerization zone is 105°C and the polymerization time is 100 min; the temperature of the holding zone is 105°C and the holding time is 100 min; S6. Place the acrylic plate coated with the coating slurry in a 365nm UV lamp box to initiate polymerization for 2.2 hours, then soak it in an ethanol-water mixed solution (the volume ratio of ethanol to water is 1:1). After 38 minutes, soak it in distilled water for 24 hours, and finally dry it at 60°C to obtain a high-hardness acrylic plate.
[0034] Comparative Example 1 This comparative example provides a continuously cast acrylic plate. The preparation method is the same as that of Example 1. The difference from Example 1 is that, in the process of preparing the coating slurry, the terminal hydroxy ether polysiloxane is replaced with a terminal hydroxy hydrocarbon polysiloxane, as follows: S1. Mix 15.5 g (10 mmol) of terminal hydrogen silicone oil and 1.72 g (20 mmol) of tetraene dipentanol and stir evenly, heat to 50°C, add 0.026 g of Karstedt catalyst, and then heat to 60°C for 4 h. After the reaction is complete, evaporate under pressure at 10 mbar to obtain hydroxyl-terminated polysiloxane. S2. Mix 17.22 g (10 mmol) of terminal hydroxyl polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate and 2.05 mg of catalyst dibutyltin dilaurate, and react under magnetic stirring at room temperature for 4 h to obtain a macromolecular prepolymer. Then, add 1.01 g (10 mmol) of end-capping agent N-hydroxymethyl acrylamide and 0.041 g of photoinitiator 2-hydroxy-2-methylpropiophenone, and continue stirring at room temperature in the dark for 2 h to obtain a coating slurry.
[0035] Comparative Example 2 This comparative example provides a continuously cast acrylic plate. The preparation method is the same as that of Example 1. The difference from Example 1 is that hydroxyethyl methacrylate is used as a capping agent during the preparation of the coating slurry, as follows: S1. Mix 15.5 g (10 mmol) of terminal hydrogen silicone oil and 2.04 g (20 mmol) of allyl hydroxyethyl ether and stir them evenly. Heat the mixture to 50°C, add 0.026 g of Karstedt catalyst, and then heat the mixture to 60°C for 4 h. After the reaction is complete, evaporate under pressure at 10 mbar to obtain terminal hydroxy ether polysiloxane. S2. Mix 17.54 g (10 mmol) of terminal hydroxy ether polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate and 2.10 mg of catalyst dibutyltin dilaurate, and react under magnetic stirring at room temperature for 4 h to obtain a macromolecular prepolymer. Then, add 1.31 g (10 mmol) of end-capping agent hydroxyethyl methacrylate and 0.042 g of photoinitiator 2-hydroxy-2-methylpropiophenone, and continue stirring at room temperature in the dark for 2 h to obtain a coating slurry.
[0036] Comparative Example 3 This comparative example provides a continuously cast acrylic plate. The preparation method is the same as that of Example 1. The difference from Example 1 is that, in the process of preparing the coating slurry, the terminal hydroxy ether polysiloxane is replaced with a terminal hydroxy hydrocarbon polysiloxane and hydroxyethyl methacrylate is used as a capping agent, as follows: S1. Mix 15.5 g (10 mmol) of terminal hydrogen silicone oil and 1.72 g (20 mmol) of tetraene dipentanol and stir evenly, heat to 50°C, add 0.026 g of Karstedt catalyst, and then heat to 60°C for 4 h. After the reaction is complete, evaporate under pressure at 10 mbar to obtain hydroxyl-terminated polysiloxane. S2. Mix 17.22 g (10 mmol) of hydroxyl-terminated polysiloxane, 3.33 g (15 mmol) of isophorone diisocyanate and 2.05 mg of catalyst dibutyltin dilaurate, and react under magnetic stirring at room temperature for 4 h to obtain a macromolecular prepolymer. Then, add 1.31 g (10 mmol) of end-capping agent hydroxyethyl methacrylate and 0.041 g of photoinitiator 2-hydroxy-2-methylpropiophenone, and continue stirring at room temperature in the dark for 2 h to obtain a coating slurry.
[0037] The acrylic sheets obtained in Example 1 and Comparative Examples 1-3 were subjected to hardness and transparency tests. Surface hardness test: According to GB / T 2411-2008, the acrylic sheets were subjected to hardness testing using a Shore D hardness tester. Five dispersed points were selected for measurement for each sample, and the average value was taken as the Shore hardness of the sample. Light transmittance test: According to GB / T 2410-2008, the light transmittance of the acrylic sheets at a wavelength of 600 nm was measured using a UV-visible spectrophotometer. The light transmittance and hardness test results are shown in Table 1.
[0038] Table 1 Test results of hardness and transparency of acrylic sheets in Example 1 and Comparative Examples 1-3 ; As can be seen from Table 1, the transmittance of the acrylic plate in Comparative Example 1 is significantly lower than that in Example 1. This is because the amide group in the end-capping agent causes poor compatibility between the polymer network of the oil-biased phase and the end-capping agent, which in turn leads to a decrease in transparency. The hardness of the acrylic plate in Comparative Example 2 is significantly lower than that in Example 1, indicating that the addition of the amide group in the end-capping agent is beneficial to improving the hardness of the high hardness layer. Comparative Example 3 is based on Comparative Example 2, but the end-hydroxy ether polysiloxane is replaced with end-hydroxy hydrocarbon polysiloxane. The transparency of the obtained acrylic plate is similar to that of Examples 1 and 2, and is slightly higher, further illustrating that the alkyl ether structure can avoid the decrease in transparency caused by the poor compatibility between the polymer network of the oil-biased phase and the end-capping agent caused by the amide group.
[0039] Comparative Example 4 This comparative example provides a continuous casting acrylic sheet. The difference from Example 1 is that no coating slurry is used, and an acrylic sheet without a high hardness layer is obtained. Specifically, the following steps are included: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 43.05 g (0.5 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine (TEA) and 0.13 g of polymerization inhibitor hydroquinone under stirring, and react at 95°C for 8 hours. After the reaction is completed, cool to room temperature, add 20 mL of deionized water to quench the catalyst, wash the reactants with water, let them stand and separate, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2, using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 55.56 mL of the modifying monomer, and 5.05 mL of n-butyl methacrylate were mixed, 0.56 g of azobisisobutyronitrile as an initiator was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry; S3, injecting the prepolymer slurry between two synchronously running endless steel belts, and during the movement of the endless steel belts, the prepolymer slurry passes through the first polymerization zone, the second polymerization zone, the heat preservation zone and the cooling zone in sequence to obtain an acrylic sheet; the continuous casting preparation method of the acrylic sheet is the existing technology; Among them, the temperature of the first polymerization zone is 60°C, and the polymerization time is 1440 minutes; the polymerization temperature of the second polymerization zone is 100°C, and the polymerization time is 1440 minutes; the temperature of the insulation zone is 100°C, and the insulation time is 1440 minutes.
[0040] Comparative Example 5 This comparative example provides a continuous casting acrylic plate. The preparation method is the same as that of Comparative Example 4, except that ethyl methacrylate is used as a modifying monomer in the process of preparing the prepolymer slurry, as follows: Ethyl methacrylate was used as a modifying monomer, 500 mL of methyl methacrylate, 55.56 mL of the modifying monomer, and 5.05 mL of n-butyl methacrylate were mixed, 0.56 g of an initiator, azobisisobutyronitrile, was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry.
[0041] Comparative Example 6 This comparative example provides a continuous casting acrylic plate, and its preparation method is the same as that of Comparative Example 4, except that, in the process of preparing the prepolymer slurry, the volume ratio of the modified monomer siloxane-modified methacrylic acid and methyl methacrylate is 2:8, as follows: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 43.05 g (0.5 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 95°C for 8 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2. Using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 125 mL of the modifying monomer, and 5.05 mL of n-butyl methacrylate were mixed, 0.63 g of azobisisobutyronitrile as an initiator was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry.
[0042] Comparative Example 7 This comparative example provides a continuous casting acrylic plate. The preparation method is the same as that of Comparative Example 4, except that, in the process of preparing the prepolymer slurry, the volume ratio of the modified monomer siloxane-modified methacrylic acid and methyl methacrylate is 0.5:9.5, as follows: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 43.05 g (0.5 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 95°C for 8 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2. Using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 26.32 mL of the modifying monomer, and 5.05 mL of n-butyl methacrylate were mixed, 0.53 g of an initiator, azobisisobutyronitrile, was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry.
[0043] Comparative Example 8 This comparative example provides a continuous casting acrylic plate. The preparation method is the same as that of Comparative Example 4, except that, in the process of preparing the prepolymer slurry, the volume ratio of the modified monomer siloxane-modified methacrylic acid and methyl methacrylate is 0.1:9.9, as follows: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 43.05 g (0.5 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 95°C for 8 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2. Using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 5.05 mL of the modifying monomer, and 5.05 mL of n-butyl methacrylate were mixed, 0.51 g of an initiator, azobisisobutyronitrile, was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry.
[0044] Comparative Example 9 This comparative example provides a continuous casting acrylic plate. The preparation method is the same as that of Comparative Example 4, except that, in the process of preparing the prepolymer slurry, the volume ratio of the modified monomer siloxane-modified methacrylic acid and methyl methacrylate is 3:7, as follows: S1. Dry the condenser, stirrer and three-necked flask in an oven at 120°C for 2 hours, assemble them while hot and purge with nitrogen, add 118.17 g (0.5 mol) of γ-glycidoxypropyltrimethoxysilane and 43.05 g (0.5 mol) of methacrylic acid, add 0.97 g of catalyst triethylamine and 0.13 g of polymerization inhibitor hydroquinone under stirring, react at 95°C for 8 hours, cool to room temperature after the reaction is completed, add 20 mL of deionized water to quench the catalyst, wash the reactants with water and let them stand for stratification, separate the organic phase and dry it with sodium sulfate to obtain siloxane-modified methacrylic acid; S2. Using siloxane-modified methacrylic acid as a modifying monomer, 500 mL of methyl methacrylate, 214.29 mL of the modifying monomer, and 5.05 mL of n-butyl methacrylate were mixed, 0.72 g of initiator azobisisobutyronitrile was added thereto, and the mixture was stirred and mixed to obtain a prepolymer slurry.
[0045] The acrylic sheets obtained in Comparative Examples 4-9 were subjected to hardness and transparency tests. Surface hardness test: According to GB / T 2411-2008, the acrylic sheets were subjected to hardness tests using a Shore D hardness tester. Five scattered points were selected for measurement for each sample, and the average value was taken as the Shore hardness of the sample. Light transmittance test: According to GB / T 2410-2008, the light transmittance of the acrylic sheets at a wavelength of 600 nm was measured using a UV-visible spectrophotometer. The light transmittance and hardness test results are shown in Table 2.
[0046] Table 2 Hardness and transmittance results of acrylic plates in comparative examples 4-9 ; As can be seen from Table 2, in Comparative Example 5, methacrylate is used as a modifying monomer to copolymerize and modify polymethyl methacrylate, and the hardness of the obtained acrylic substrate is the lowest. In Comparative Examples 7 and 8, the amount of the modified monomer siloxane-modified methacrylic acid is reduced compared with Comparative Example 4, and the hardness of the obtained acrylic board is somewhat lower than that of Comparative Example 4, while the transmittance is similar to that of Comparative Example 4, indicating that the modified monomer siloxane-modified methacrylic acid can increase the hardness of the acrylic board and has little effect on the transmittance of the acrylic board under certain conditions.
[0047] In Comparative Examples 6 and 9, the amount of modified monomer siloxane-modified methacrylic acid is increased compared with Comparative Example 4. The hardness of the obtained acrylic plate is slightly higher than that of Comparative Example 4, but the transmittance is greatly reduced. This is because the compatibility of siloxane-modified methacrylic acid with methyl methacrylate is poor, resulting in uneven dispersion of the system and easy agglomeration, thereby affecting the transmittance of the material.
[0048] The specific embodiments of the present invention described above do not limit the scope of protection of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a continuous casting high-hardness acrylic sheet, characterized in that: The following steps are involved: S1, mixing siloxane-modified methacrylic acid, methyl methacrylate, and n-butyl methacrylate, adding an azo initiator thereto, and stirring and mixing to obtain a prepolymer slurry; S2, mixing the hydroxy-terminated ether polysiloxane, isophorone diisocyanate and the catalyst dibutyltin dilaurate, and reacting them under magnetic stirring at room temperature for 4 to 6 hours to obtain a macromolecular prepolymer, and then adding the end-capping agent N-hydroxymethyl acrylamide and the photoinitiator 2-hydroxy-2-methylpropiophenone thereto, and continuing to stir at room temperature in the dark for 2 hours to obtain a coating slurry; S3. The prepolymer slurry is injected between two synchronously running endless steel belts, and the coating slurry is coated on the two endless steel belts at the same time. During the operation of the endless steel belts, the prepolymer slurry is continuously polymerized through the first polymerization zone and the second polymerization zone, and then is kept warm in the heat preservation zone and cooled in the cooling zone to obtain an acrylic plate coated with the coating slurry. The acrylic plate coated with the coating slurry is cured by ultraviolet light to obtain a high-hardness acrylic plate.
2. The method for preparing a continuously cast high-hardness acrylic sheet according to claim 1, characterized in that: In step S1, the volume ratio of the siloxane-modified methacrylic acid to methyl methacrylate is 1-1.2:9, and the n-butyl methacrylate accounts for 1-20% of the total volume of the methyl methacrylate and n-butyl methacrylate.
3. The method for preparing a continuous casting high-hardness acrylic plate according to claim 1, characterized in that: In step S1, the preparation method of the siloxane-modified methacrylic acid is as follows: drying a condenser, a stirrer, and a three-necked flask in an oven at 120° C. for 2 hours, assembling them while hot and purging them with nitrogen, adding γ-glycidoxypropyltrimethoxysilane and methacrylic acid, adding a catalyst triethylamine and a polymerization inhibitor hydroquinone under stirring, reacting at 95° C. to 105° C. for 4 to 8 hours, cooling to room temperature after the reaction is completed, adding deionized water to quench the catalyst, washing the reactants with water, standing them for stratification, separating the organic phase, and drying them to obtain the siloxane-modified methacrylic acid.
4. The method for preparing a continuously cast high-hardness acrylic plate according to claim 3, characterized in that: The molar ratio of the γ-glycidoxypropyltrimethoxysilane to methacrylic acid is 1:1-1.05, the amount of triethylamine added is 0.6% of the total mass of the γ-glycidoxypropyltrimethoxysilane and methacrylic acid, and the mass ratio of the hydroquinone to the triethylamine is 2:
15.
5. The method for preparing a continuously cast high-hardness acrylic plate according to claim 1, characterized in that: The UV curing method specifically includes: initiating polymerization of the acrylic plate coated with the coating slurry under 365nm UV light for 2-2.5 hours, then soaking it in a mixed solution of ethanol and water for 30-45 minutes, then soaking it in distilled water for 24 hours, and finally drying it at 60°C.
6. The method for preparing a continuously cast high-hardness acrylic plate according to claim 1, characterized in that: The temperature of the first polymerization zone is 60~80℃, and the polymerization time is 5~1440min; the polymerization temperature of the second polymerization zone is 100~140℃, and the polymerization time is 5~1440min; the temperature of the holding zone is 100~140℃, and the holding time is 5~1440min.
7. The method for preparing a continuously cast high-hardness acrylic plate according to claim 1, characterized in that: In step S2, the preparation method of the terminal hydroxy ether polysiloxane is as follows: terminal hydrogen silicone oil and allyl hydroxyethyl ether are mixed and stirred uniformly, heated to 50° C., Karstedt catalyst is added thereto, and then heated to 60-70° C. for reaction for 3-4 hours. After the reaction is completed, pressure rotary evaporation is performed at 10-50 mbar to obtain the terminal hydroxy ether polysiloxane.
8. The method for preparing a continuously cast high-hardness acrylic plate according to claim 7, characterized in that: The hydrogen content of the hydrogen-terminated silicone oil is 0.11-0.13%, the molar ratio of the hydrogen-terminated silicone oil to the allyl hydroxyethyl ether is 1:2, and the amount of the Karstedt catalyst added is 0.15-0.2% of the total mass of the hydrogen-terminated silicone oil and the allyl hydroxyethyl ether.
9. The method for preparing a continuously cast high-hardness acrylic plate according to claim 1, characterized in that: In step S2, the molar ratio of the terminal hydroxy ether polysiloxane, isophorone diisocyanate and N-hydroxymethyl acrylamide is 1:1.5:1, the amount of the photoinitiator added is 0.2% of the total mass of the terminal hydroxy ether polysiloxane and isophorone diisocyanate, and the mass ratio of the catalyst to the photoinitiator is 0.1~0.3:
2.
10. The continuously cast high-hardness acrylic sheet prepared by the method for preparing the continuously cast high-hardness acrylic sheet according to claim 1.
Citation Information
Patent Citations
Low-temperature-resistant acrylic board
CN106543613A
Method for preparing modified WPU (Waterborne Polyurethane) coating film
CN106750162A
Modified UV-curing waterborne polyurethane acrylate coating and preparation method thereof
CN107603460A
Preparation method for amphipathic organosilicon-polyurethane grafted copolymer with comb-like structure
CN108129636A
Formula and preparation method of anti-fingerprint high-hardness bendable low-shrinkage UV hardening liquid
CN113088182A
Cited By
Continuous pouring flame-retardant acrylic plate and preparation method thereof
CN120904611A
Continuous pouring flame-retardant acrylic plate and preparation method thereof
CN120904611B